Challenges of the Anatomy and Diffusion Tensor Tractography of the Meyer Loop - Mandelstam, S.A. (American Journal of Neuroradiology, 2012)
SUMMARY: This review addresses the complex and often controversial anatomy of the anterior bundle of the OR, also known as the Meyer loop. Before the advent of MR imaging, 2 main types of studies attempted to ascertain the “safe” distance for anterior temporal lobe resection to avoid postsurgical VFDs. There were those based first on postoperative VFD correlation and second on anatomic dissection studies. In the past decade, noninvasive diffusion MR imaging−based tractography techniques have been developed in an attempt to elucidate white matter connectivity. Although many of these techniques are still experimental, there are some clinical situations for which they may prove to be very helpful if properly performed and validated. The motivation for this review was to improve the outcome of patients with TLE undergoing temporal lobectomy: Would having anatomic information about the OR available to the neurosurgeon decrease the risk of postsurgical VFDs? ATLanterior temporal lobectomyCSDconstrained spherical deconvolutionDT-FTdiffusion tensor fiber tractographyDTIdiffusion tensor imagingFAfractional anisotropyLGBlateral geniculate bodyLGNlateral geniculate nucleusORoptic radiationsTLEtemporal lobe epilepsyTPtemporal poleVFDvisual field deficit